Creation and Training of artifical neural network for Detection and Neutralization of Network DDos–attacks(“Denial of Service”) - P. V. Razumov; L. V. Cherkesova; E. A. Revyakina (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The goal of the research is to develop an artificial neural network (ANN) to detect and neutralize network DDoS attacks.Method. The research is based on the use of the Python programming language in an environment that supports the training functions of PyCharm neural networks.Result. An analysis of existing artificial neural networks was carried out to determine their optimal structure; Existing methods for detecting network DDoS attacks have been studied; Datasets were collected and refined to improve the quality of training; The structure of the artificial neural network of the classifier was created and its training was carried out, a demonstration software was created that illustrates the process of classification and blocking and neutralizing DDoS attacks.Conclusion. Having systems to monitor traffic, a Web application firewall, speed limiting, a status page, and a company face to answer questions on social media will all help ensure the most effective protection against DDoS attacks.